2013
DOI: 10.1038/cdd.2012.158
|View full text |Cite|
|
Sign up to set email alerts
|

Acidotoxicity and acid-sensing ion channels contribute to motoneuron degeneration

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological condition with no cure. Mitochondrial dysfunction, Ca 2 þ overloading and local hypoxic/ischemic environments have been implicated in the pathophysiology of ALS and are conditions that may initiate metabolic acidosis in the affected tissue. We tested the hypothesis that acidotoxicity and acid-sensing ion channels (ASICs) are involved in the pathophysiology of ALS. We found that motoneurons were selectively vulnerable to acidotoxicity in vitro, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…1E). Our data on increasing acidosis within the lumbar spinal cord agree with recent findings in C57BL/6 SOD1 G93A mice by an alternative pH measuring method (14). Thus, as the mouse ALS disease advanced, the CNS developed progressively greater acidosis.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1E). Our data on increasing acidosis within the lumbar spinal cord agree with recent findings in C57BL/6 SOD1 G93A mice by an alternative pH measuring method (14). Thus, as the mouse ALS disease advanced, the CNS developed progressively greater acidosis.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, gene expression profiling studies showed significant up-regulation (2-to 10-fold) of ASIC2 (also known as amiloride-sensitive cation channel neuronal 1; ACCN1) and ASIC3 (ACCN3) in laser-captured motor neurons from patients with ALS harboring mutations in SOD1 (13), suggesting that acidosis occurs in patients with ALS. In agreement, significant upregulation of ASIC2 expression was recently noted in the spinal cords of patients with sporadic ALS and SOD1 G93A mice (14).…”
supporting
confidence: 84%
“…Concomitant with reduced pH, significant accumulation of glycogen was observed in both the CNS and visceral organs of SOD1 G93A mice [46]. Furthermore, treatment of SOD1 G93A mice with acetazolamide which promotes acidosis worsened survival [46], while deletion or pharmacological inhibition of acid sensing ion channels improved symptoms [65], suggesting a deleterious role of metabolic acidosis in ALS.…”
Section: Glucose and Atp Metabolism In Mutant Sod1 Micementioning
confidence: 99%
“…10,13,15 It was reported that compared with WT mice, ASIC1a-deficient mice had both a markedly reduced motor deficit and decreased axonal degeneration in a mouse model of experimental autoimmune encephalomyelitis despite the similar levels of CNS inflammation. 39,43 Interestingly, ASIC1a was found only in the surface membrane of neuronal soma and dendrites but not that of axons. 3,44 Perturbed intracellular Ca 2 þ homeostasis was considered as a major underlying cause of this disease.…”
Section: Discussionmentioning
confidence: 99%